Perancangan Set Mebel Rumah Tinggal Dengan Konsep Filosofi Tato Dayak - Filipus Priyo Suprobo, Linda Wong Adi Santosa (Intra, 2014)
Dayak is one of the ethnic groups in Indonesia which has a fairly high cultural value. Among the many ethnic groups in Indonesia, the Dayak tribes became the oldest and the only original tribes of Borneo. Dayak tribe has its own traditions and cultural traits, namely as a tradition that has always been their ancestral worship; body or merajak tradition known as tattoos, which are now known as âBorneo Tattooâ society;, the tradition of letting their ears, and much more to culture and traditions. But the tradition and culture that the rich are now extinct, they had long abandoned their traditions and culture. The appointment of these themes to cultural traditions and reintroduced the Dayak community to Indonesia with the existence or the more modern packaging however contain cultural values in it.